Role of Ninik Mamak in the Prevention and Control of HIV/AIDS in Minangkabau - Handayani, Sri; Angelia, Inge; Fitri, Wiya Elsa (PT. Riset Press International, 2024)
Background: West Sumatra is ranked 19th regarding the highest number of HIV cases with 541 HIV cases and 258 AIDS cases. Meanwhile in the city of Padang the HIV incidence rate in 2019 was 287 cases. Objective: Is there a relationship between the role of Ninik Mamak and HIV/AIDS risk behavior? Results: As many as 59.61% of respondents behaved at risk of HIV/AIDS and as many as 51.92% of respondents stated that Ninik Mamak played a role in controlling HIV/AIDS. There is a relationship between the role of Ninik Mamak and HIV/AIDS risk behavior (P-value = 0.002). Conclusion: There is a relationship between the role of Ninik Mamak and HIV/AIDS risk behavior.